Arachidonic acid is associated with dyslipidemia and cholesterol-related lipoprotein metabolism signatures - Li, Fan; Wang, Yu; Yu, Huahui; Gao, Xiaoqian; Li, Linyi; Sun, Haili; Qin, Yanwen (Frontiers in Cardiovascular Medicine, 2022)
Abnormal lipoprotein metabolism is associated with a variety of diseases, and cardiovascular disease in particular. Free fatty acids (FAs) and triglycerides (TGs) are the principal lipid species in adipocytes and are the major components of lipoproteins. However, in routine clinical laboratory testing, only the total plasma concentrations of FAs and TGs are typically measured. High-throughput metabolomics permits the accurate qualitative and quantitative assessment of a variety of specific FAs and TGs and their association with lipoproteins. Here, we studied the relationships of eight FA and 27 TG species with the plasma lipid concentrations of 965 individuals with hyperlipidemia, and found that the plasma concentrations of free arachidonic acid (AA) and AA-enriched TG species were significantly associated with the plasma low-density lipoprotein-cholesterol, apolipoprotein B (ApoB), and total cholesterol (TC) concentrations after adjustment for age, sex, the use of lipid-lowering therapy, and body mass index. We next aimed to determine the effect of AA consumption on the plasma cholesterol concentration and key regulators of cholesterol metabolism, and we found that an AA-rich diet significantly increased the plasma concentrations of TC and ApoB and the liver expression of ApoB protein, and reduced the protein expression of ATP binding cassette subfamily G members 5 and 8 in mice. Taken together, these findings suggest a potential role of AA in the regulation of plasma cholesterol and lipoprotein concentrations.